PENGEMBANGAN E-MODUL BERBASIS KEARIFAN LOKAL MATERI MOMENTUM DAN IMPULS SMA KELAS X - Rahma Dani; Jufrida Jufrida; Fibrika Rahmat Basuki; Uliya Aprily (Physics Education Departement Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2022)
This study aims to develop an e-module based on local wisdom for the momentum and impulses of Class X SMA. This research was a research and development that uses a 4-D development model consisting of 4 stages, namely Define, Design, Develop, and Disseminate. The subjects of this study were 2 material experts and media experts, as well as class X students at SMA Negeri 2 Jambi City, totaling 35 students. There were 2 types of data obtained, namely qualitative data and quantitative data. The instruments used in this study were observation sheets, interview sheets, material and media expert validation sheets and student perception questionnaires. Qualitative data were analyzed descriptively and quantitative data were analyzed using descriptive statistics. This research produces e-modules based on local wisdom material on momentum and impulse. Jambi's local wisdom is used as a context to explore the concepts of momentum and impulse. The results of material validation obtained a percentage of 95.63% in the